(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
The present research aims at investigating the economic performance of mixed ricefish farming in south-west region of Bangladesh. In order to carry out the research objective descriptive statistics, profit function, Cobb-Douglas form of multiple linear regression model and t-test approaches have been applied. The study area has been selected using multi-stage sampling technique and convenient sampling method has been utilized to select the sample. In-depth interview technique has been employed to collect primary data by using pretested questionnaire from the samples. Results from descriptive statistics show that the average annual return on mixed rice-fish farming is BDT 56326.45 more than mono rice farming as well as production efficiency of mixed rice-fish farming is also found higher than mono rice farming. Besides, mixed rice-fish farming experiences increasing return to scale, whereas, mono rice farming undergoes decreasing return to scale. Moreover, test of hypothesis provides statistical evidence that mixed rice-fish farming is more profitable than mono rice farming in the study area. Res. Agric., Livest. Fish.3(3): 453-462, December 2016